PENGARUH KEBIJAKAN PPKM, INSENTIF, DAN FLEXTIME TERHADAP PENDAPATAN PENGEMUDI GOJEK MASA PANDEMI COVID-19 DI DENPASAR - Prasetyo, Muhamad Wahyu; Yasa, I Nyoman Mahaendra (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2024)
The purpose of the study was to analyze the effect of the Policy for Enforcement of Community Activity Restrictions (PPKM), incentives, and flexible working hours (Flextime) on the income of Gojek drivers during the Covid-19 pandemic in Denpasar City. This research was conducted in Denpasar City using primary data obtained from distributing questionnaires to Gojek drivers in Denpasar City with a total sample of 95 Gojek drivers and using purposive sampling method. The data collected was then analyzed using descriptive statistical analysis techniques and multiple linear regression. The results showed that the policy variables for the application of PPKM, incentives, and flextime had a significant simultaneous effect on the income of Gojek drivers during the Covid-19 pandemic in Denpasar City. The PPKM Policy has a negative significant effect, while Incentives and Flextime have a positive significant impact on the income of Gojek drivers during the Covid-19 pandemic in Denpasar City.